Performance of lactating dairy cattle in three different cooling systems - Meyer, M. J.; Smith, John F., 1962-; Harner, Joseph P.; Titgemeyer, Evan C.; Shirley, John E. (Kansas Agricultural Experiment Station and Cooperative Extension Service., 2011)
Ninety-six Holstein multiple-lactation cows averaging 115 days in milk (DIM) and 60 Holstein first-lactation cows averaging 97 DIM at the initiation of a 10-wk study between June 10 and August 22, 1998 were used to evaluate the effectiveness of three different cooling systems. Thirty-two multiparous cows and 20 first-lactation cows were assigned to each of three pens that contained different cooling systems. The three cooling systems consisted of : 1) a single row of 36-inch fans, spaced at 24-ft intervals over the freestalls and over the feed row, 2) 56-inch ceiling fans spaced at 12-ft intervals over the freestalls, and 3) polytube longitudinal cooling over the freestalls. Each of the three cooling systems utilized similar sprinkler systems located over the feed line. Dry matter intake, respiration rates, milk production, and body condition scores were measured. Cows cooled with overhead 36-inch fans produced more milk and had lower respiration rates than those cooled with other methods. The cows cooled with ceiling fans tended to produce more milk than those cooled via the polytube. Dry matter intake also tended to be greater for cows cooled by overhead 36-inch fans.
Keywords: Heat stress; Dairy; Milk production; Cooling